Antibacterial Efficacy of 940 nm Diode Laser against Cariogenic Bacteria (Tooth Decay-causing Bacteria) - Noha M. Jameel; Hanan J. Taher (مجلة بغداد للعلوم)
Dental caries is an extremely prevalent infectious disease caused by gram-positive bacteria mainly streptococcus mutans which is considered the major etiological factor causing dental caries. In recent years, there has been an enormous increase in the use of laser technology in medicine and dentistry and it has been demonstrated to have a considerable antibacterial action with no harm to the oral tissues. The study goal was to assess a diode laser's effectiveness as an antibacterial agent against the bacterium species S. mutans at various doses. The study was performed on streptococcus mutans microorganism at 106 CFU/ml concentration which received irradiation from a diode laser with 940 nm a central wavelength to investigate three output powers (1 watt, 2 watts, and 3 watts) for 30 s exposure time, and chlorohexidine (CHX) was used as a positive control group. Bacterial growth (CFU/ml) was calculated 24 hours after laser exposure. A significant diminish in CFUs/ml of S. mutans bacteria was observed 24 hours following irradiation by the three different powers. The result showed a statistical difference (p-value < 0.01) as compared to the negative control group without treatment. The current study demonstrated that the 940 nm diode laser was successful and efficient in the reduction of S. mutans growth at different doses